Reduced kidney size and renal function of high-grade vesicoureteral reflux and intrarenal reflux in contrast-enhanced voiding urosonography - Yan, Hualin; Wu, Cong; Zhou, Jiehong; Huang, Cairong; Ma, Xue; Huang, Yidong; Huang, Lugang; Liu, Juxian (Frontiers in Pediatrics, 2024)
BackgroundVesicoureteral reflux (VUR) is a common pediatric urological condition associated with renal scarring, hypertension, and chronic kidney disease. Contrast-enhanced voiding urosonography (ceVUS) has emerged as a promising technique for diagnosing and evaluating VUR, with intrarenal reflux (IRR) often detected using this method. This study aimed to explore the relationship between different VUR grades and IRR on ceVUS, and assess the impact of VUR and IRR on kidney size and function.MethodsWe reviewed all ceVUS studies from January 2019 to December 2023 conducted at West China Hospital, Sichuan University. Both video clips and digital images of the ceVUS examinations were recorded. A total of 220 uretero-renal units (URUs) of 110 children (67 males and 43 females) were included in this study.ResultsAmong the 220 URUs assessed, 134 were diagnosed with VUR, and 25 exhibited IRR, with IRR exclusively observed in patients with grade II VUR or higher. Upon age and sex matching, the severity of IRR showed a significant positive correlation with high-grade VUR (P < 0.001). Notably, patients with high-grade VUR and IRR displayed reduced kidney size compared to those without VUR or IRR (P < 0.05). Furthermore, patients with high-grade VUR and IRR had reduced DMSA renal function (P = 0.015, P = 0.012, respectively), and patients with high-grade VUR had more DMSA scars (P = 0.027), compared with those without VUR or IRR.ConclusionOur study highlights that on ceVUS, the IRR degree was associated with the high-grade VUR, along with reductions in kidney size and renal function in patients with high-grade VUR and IRR.